Epidemiology of disorders of Gut‐Brain interaction in Israel: Results from the Rome Foundation global epidemiology study. Issue 8 (24th January 2022) - Sperber, Ami D.; Freud, Tamar; Abu‐Freha, Naim; Shibli, Fahmi; Brun, Rita; Bangdiwala, Shrikant I.; Palsson, Olafur S.; Dickman, Ram
Abstract: Background: Data for Israel from the Rome Foundation Global Epidemiology Study on the disorders of gut‐brain interaction (DGBI) were used to assess the national prevalence of all 22 DGBI, the percentage of respondents meeting diagnostic criteria for at least one DGBI, and the impact on burden of disease in Israel. Methods: The survey was conducted through the Internet with multiple built‐in quality‐assurance techniques and included the Rome IV diagnostic questionnaire and an in‐depth supplemental questionnaire. Key Results: 2012 Israeli participants completed the survey nationwide: mean age 44.6 ± 16.4 years, 50% females. The national distribution was very close to the latest Israeli census. 36.4% (95% CI 34.3, 38.4) met diagnostic criteria for at least one DGBI, with 4.4% for any esophageal disorder, 6.5% for any gastroduodenal disorder, 30.8% for any bowel disorder, and 5.3% for any anorectal disorder. The rates were higher for women. Having any DGBI was associated negatively with psychosocial variables (including quality of life, somatization, and concern about digestive problems), and healthcare utilization (including doctor visits, use of medications, and abdominal surgeries). Conclusions & Inferences: The results of this study provide the first in‐depth assessment of the prevalence and burden of Rome IV DGBI in Israel and facilitate comparisons with other countries. As 36.4% of the 2, 012 participants met diagnostic criteria for at least one DGBI, and 23.5% of those met criteria for more than one DGBI, the burden of DGBI in Israel is high, indicating a need to focus on research and training for patient care. Abstract : The results of this study provide an in‐depth assessment of the prevalence and burden of DGBI in Israel and facilitate comparisons with other participating countries. As 36.4% of the 2, 012 participants met diagnostic criteria for at least one DGBI, and 23.5% of those met criteria for more than one DGBI, their burden in Israel is high, indicating a need to focus on research and on training for patient care. The figure shows a comparison of prevalence rates (%) for DGBI by anatomical GI region between Israel ( N = 2012) and the other 25 countries ( N = 52, 115). Although the rates are different, the rankings within each region are similar.